(untitled) (Cardiovascular Journal, 2022)
Background: Hypertension is the leading cause of cardiovascular morbidity and mortality all over the world. Although some epidemiological studies on hypertension have been conducted in Bangladesh, the factors associated with hypertension in this nation remain unclear. The objective of this study was to determine the factors associated with hypertension among the adult population in a northern district in Bangladesh. Methods: This cross- sectional study was conducted at the Department of Cardiology, M. Abdur Rahim Medical College Hospital, Dinajpur from March 2021 to February 2022. Out of total of 500 participants from OPD and indoor Cardiology Department of this hospital, 250 hypertensive patients were recruited as cases and another 250 normotensive participants were taken as control. Results: Majority of the hypertensive patients in the study population were in 46-55 years of age group [male 48(32.4%) and female 40(39.2%)]; whereas normotensive participants less in number in the same age group [male 20(16.1%) and female 24(19.0%)]. Hypertension was more common in males (59.2% of cases). Moreover, hypertensive participants had strong family history (66%) of hypertension, urban residential area (68%), habits of smoking (67.2%), diabetes mellitus (64%), and excess salt consumption (70%). Raised levels of total cholesterol, triglycerides, and LDL were more common among hypertensive participants than that of the normotensive control group and which was found to be statistically significant. Conclusion: Our study shows that the risk of hypertension was significantly associated with older age, male sex, family history of hypertension, urban residence, smoking, excess salt consumption, higher BMI and waist circumference, dyslipidemia and diabetes mellitus. More studies and area-specific longitudinal research is needed in this field which would help adopt national policies to limit incidence as well as consequences of hypertension in our country. Cardiovasc j 2022; 15(1): 69-74